Epigallocatechin-3-Gallate Attenuates Myocardial Dysfunction via Inhibition of Endothelial-to-Mesenchymal Transition - Sejin Kim; Hyunjae Lee; Hanbyeol Moon; Ran Kim; Minsuk Kim; Seongtae Jeong; Hojin Kim; Sang Hyeon Kim; Soo Seok Hwang; Min Young Lee; Jongmin Kim; Byeong-Wook Song; et al. (MDPI AG, 2023)
Cardiac tissue damage following ischemia leads to cardiomyocyte apoptosis and myocardial fibrosis. Epigallocatechin-3-gallate (EGCG), an active polyphenol flavonoid or catechin, exerts bioactivity in tissues with various diseases and protects ischemic myocardium; however, its association with the endothelial-to-mesenchymal transition (EndMT) is unknown. Human umbilical vein endothelial cells (HUVECs) pretreated with transforming growth factor β2 (TGF-β2) and interleukin 1β (IL-1β) were treated with EGCG to verify cellular function. In addition, EGCG is involved in RhoA GTPase transmission, resulting in reduced cell mobility, oxidative stress, and inflammation-related factors. A mouse myocardial infarction (MI) model was used to confirm the association between EGCG and EndMT in vivo. In the EGCG-treated group, ischemic tissue was regenerated by regulating proteins involved in the EndMT process, and cardioprotection was induced by positively regulating apoptosis and fibrosis of cardiomyocytes. Furthermore, EGCG can reactivate myocardial function due to EndMT inhibition. In summary, our findings confirm that EGCG is an impact activator controlling the cardiac EndMT process derived from ischemic conditions and suggest that supplementation with EGCG may be beneficial in the prevention of cardiovascular disease.